Nurse’s Individual Factors May Predict Quality of Nursing Work Life (Qnwl) in Clinical Setting - Faizin, Riyanto; Fitryasari, Rizki; Wahyuni, Erna Dwi; Nursalam, Nursalam (International Journal of Psychosocial Rehabilitation, 2020)
Quality of Nursing Work Life (QNWL) affects organizational productivity. Low nurse’s QNWL level will decrease employer’s commitment to work and reach the hospital vision. The aim of the study was to analyze the relationship of nurse’s individual factors with QNWL. The study design was descriptive correlation with cross sectional approach. The population was nurses at the Lamongan Muhamadiyah Hospital and 166 respondents were obtained through purposive sampling techniques. Variables were individual factors and QNWL. The instrument used was individual factors questionnaire and included age, gender, education level, number of children, dependents, job position, work period, works experience and motivation. The Brooks’s questionnaire was used to measure nurse QNWL. Data were analyzed by logistic regression test. Individual factors related to QNWL are age (p = 0.043), gender (p = 0.001), level of education (p = 0.048), number of children (p = 0.023), dependents (p = 0.034), job position (p = 0.014), work period (p = 0.038), work experience (p = 0.026) and motivation (p = 0.008). Motivation was are the most dominant and affects to QNWL. It was 8,945 times compared to other factors. Motivation fosters enthusiasm for nurses to demonstrate their ability to carry out their duties and the hope for obtaining rewards and job promotions from superiors that have an impact on improving the quality of life as a nurse. Management, especially in the nursing resources section, needs to keep nurses’ motivation in carrying out daily tasks.